Positive electrode material and electrochemical device and electronic device using the same

By forming a structure covering the rock salt phase layer on the surface of the lithium-ion battery cathode material, the problem of insufficient structural stability and electrochemical stability of the cathode material under high voltage is solved, and better cycle performance and safety performance are achieved.

CN114551857BActive Publication Date: 2025-01-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210106979.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-25
Publication Date
2025-01-21
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

Under high voltage conditions, the positive electrode surface of lithium-ion batteries is prone to produce by-products, affecting its cycling and safety performance. The structural stability and electrochemical stability of traditional lithium cobalt oxide cathode materials are poor.

Method used

A new cathode material is used, the surface of which is covered with a rock salt phase layer. The rock salt phase layer contains oxygen element, and the ratio to the mass percentage of oxygen element in the matrix is ​​between 0.15 and 0.65. It has the ability to conduct ions and limits The ability to dissolve oxygen.

Benefits of technology

It improves the structural stability and cycle performance of the cathode material, maintains excellent electrochemical performance under high voltage, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114551857B_ABST
    Figure CN114551857B_ABST
Patent Text Reader

Abstract

The present application relates to the field of energy storage technology, and in particular to a positive electrode material and an electrochemical device and electronic device using the same. The positive electrode material comprises: a substrate; and a surface layer covering at least part of the surface of the substrate, the surface layer comprising a rock salt phase layer; the mass percentage of oxygen element in the rock salt phase layer is W1, the mass percentage of oxygen element in the substrate is W2, and the ratio of W1 to W2, W1 / W2, is 0.15 to 0.65. The positive electrode material of the present application has good structural stability, which helps to improve the cycle performance of the electrochemical device under high voltage working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is a divisional application filed for an application with a filing date of November 25, 2020, an application number of 202011339825.8, and an application name of “Positive electrode materials and electrochemical devices and electronic devices using the same”.

[0002] The present application relates to the field of energy storage technology, and in particular to a positive electrode material and an electrochemical device and an electronic device using the same. Background Art

[0003] Electrochemical devices (e.g., lithium-ion batteries) are widely used in mobile phones, computers, wearable devices, drones, electric vehicles, and large energy storage devices due to their advantages such as high energy density, long cycle life, and no memory effect. With the development of technology and the increase in demand for these devices, people's demand for electrochemical devices has increased significantly. The development of lithium-ion batteries with good cycle stability and storage performance at high voltage is one of the research directions in the field of lithium-ion batteries.

[0004] Among them, the positive electrode material, as an important component of lithium-ion batteries, has a significant impact on its performance, so the continuous optimization and improvement of positive electrode materials is particularly important. Under high-voltage working conditions, the positive electrode surface of lithium-ion batteries is prone to produce by-products, which affects the cycle performance of lithium-ion batteries. For example, when traditional lithium cobalt oxide positive electrode materials work under high voltage conditions, their structural stability and electrochemical stability are poor, which will significantly reduce the electrochemical performance and safety performance of the battery, making it difficult to meet people's demand for the use of lithium-ion batteries.

[0005] In view of the above, there is a real need to provide an improved positive electrode material having excellent high voltage stability and an electrochemical device comprising the same. Summary of the invention

[0006] The purpose of the present application is to provide a positive electrode material and an electrochemical device and an electronic device using the same. The positive electrode material has a special surface structure, good structural stability, and thus good high voltage stability, and can solve at least one problem existing in the related field to at least some extent.

[0007] According to the first aspect of the present application, a positive electrode material is provided, comprising: a substrate; and a surface portion covering at least a portion of the surface of the substrate, the surface portion comprising a rock salt phase layer; wherein the mass percentage content of oxygen element in the rock salt phase layer is W1, the mass percentage content of oxygen element in the substrate is W2, and the ratio of W1 to W2, W1 / W2, is 0.15 to 0.65.

[0008] According to some embodiments of the present application, the rock salt phase layer includes a rock salt phase and holes, and in the orthographic projection in the observation direction, the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is 0.01 to 0.7.

[0009] According to some embodiments of the present application, a ratio of a projected area of ​​the pores to a projected area of ​​the rock salt phase is 0.2 to 0.7.

[0010] According to some embodiments of the present application, the rock salt phase layer and the matrix both contain the element TM; the mass percentage content of the TM element in the rock salt phase layer is T1, the mass percentage content of the TM element in the matrix is ​​T2, and the ratio of T1 to T2 is 0.15 to 0.5, wherein the element TM includes at least one of Co, Mn or Ni.

[0011] According to some embodiments of the present application, the thickness of the rock salt phase layer is 20 nm to 200 nm.

[0012] According to some embodiments of the present application, the surface layer further includes a transition layer, which is located between the rock salt phase layer and the matrix, wherein the transition layer originates from the mutual diffusion of elements in the rock salt phase layer and the matrix.

[0013] According to some embodiments of the present application, the rock salt phase layer contains element A, and A includes at least one of F, N or Na.

[0014] According to some embodiments of the present application, the rock salt phase includes M x A y O m , wherein the M includes at least one of Co, Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn or Cr, the A includes at least one of F, N or Na, 1≤x≤6, 1≤y≤4, 0.5x≤m≤2x+y. Preferably, according to some embodiments of the present application, the M includes at least one of Co, Mn, Ni, Ti, Al and Mg.

[0015] According to some embodiments of the present application, the matrix includes a lithium transition metal composite oxide, and the composition of the lithium transition metal composite oxide is Li a Me b Co c O d-e T e, wherein, the Me includes at least one of Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn, Zr or Cr, T is a halogen, 0.2 ≤ a ≤ 1.2, 0 ≤ b ≤ 1, 0 < c ≤ 1, 1 ≤ d ≤ 2, 0 ≤ e ≤ 1. Preferably, according to some embodiments of the present application, the Me includes at least one of Mn, Ni, Ti, Al, Mg.

[0016] Preferably, according to some embodiments of the present application, the composition of the lithium transition metal composite oxide is Li a Ni b1 Mn b2 Co c O d-e T e , wherein, 0.8 ≤ a ≤ 1.2, 0 ≤ b1 + b2 ≤ 1, 0 < c ≤ 1. Preferably, according to some embodiments of the present application, the composition of the lithium transition metal composite oxide includes LiCoO 2 , LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 , LiNi 0.5 Mn 0.3 Co 0.2 O 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 , LiNi 0.6 Mn 0.2 Co 0.2 O 2 at least one of them.

[0017] Preferably, according to some embodiments of the present application, the composition of the lithium transition metal composite oxide is Li a Al b3 Mg b4 Ti b5 Co c O d-e T e , wherein, 0.8 ≤ a ≤ 1.2, 0 ≤ b3 + b4 + b5 ≤ 1, 0 < c ≤ 1. Preferably, according to some embodiments of the present application, the composition of the lithium transition metal composite oxide includes LiAl 0.01 Co 0.99 O 2 , LiAl 0.01 Mg 0.01 Ti 0.01 Co 0.97 O 2 , LiMg 0.05 Co 0.95 O2 At least one of .

[0018] According to a second aspect of the present application, an electrochemical device is provided, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes the positive electrode material described in the above embodiment of the present application.

[0019] According to some embodiments of the present application, the rock salt phase layer contains element A, and the electrolyte contains the element A, wherein A includes at least one of F, N or Na, and the difference between the mass percentage of element A in the rock salt phase layer and the mass percentage of element A in the electrolyte does not exceed 10%.

[0020] According to some embodiments of the present application, the electrochemical device is a lithium-ion battery.

[0021] According to a third aspect of the present application, an electronic device is provided, which includes the electrochemical device described in the above embodiment of the present application.

[0022] The technical solution of this application has at least the following beneficial effects:

[0023] The present application provides a positive electrode material and an electrochemical device and an electronic device comprising the positive electrode material, wherein the positive electrode material is characterized in that the surface is coated with a rock salt phase layer, the rock salt phase layer and the matrix both contain elemental oxygen, and the ratio of the oxygen content of the rock salt phase layer to the oxygen content of the matrix is ​​within a suitable range. This rock salt phase layer structure has ion conductivity and a strong ability to limit oxygen dissolution, while blocking the invasion of electrolyte, thereby increasing the structural stability of the positive electrode material and having improved cycle performance under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0025] Figure 1 A STEM image of a rock salt phase-pore of a cathode material provided for an exemplary embodiment of the present application;

[0026] Figure 2 A grayscale distribution diagram of rock salt phase-pores of a positive electrode material provided for an exemplary embodiment of the present application;

[0027] Figure 3 The element distribution diagram of the positive electrode material provided for an exemplary embodiment of the present application; wherein, Figure 3 (a) is a schematic diagram of the distribution of oxygen elements. Figure 3(b) is a schematic diagram of the distribution of cobalt element;

[0028] Figure 4 Schematic diagram of the cycle performance of the lithium-ion battery provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0029] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent descriptions through the implementation of the embodiments of the present application. The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0030] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.

[0031] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0032] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0033] Electrodes (positive or negative) of electrochemical devices (e.g., lithium-ion batteries) are typically prepared by mixing active materials, conductive agents, thickeners, binders, and solvents, and then coating the mixed slurry on a current collector. Active materials are critical to the performance of electrochemical devices because cell voltage, capacitance, and cyclability, as well as the total amount of free energy change, are generally determined by the electrode materials, which are based on the electrochemical reactions at the two electrodes depending on the materials selected at the two electrodes. In addition, the cycling performance of electrochemical devices can vary with the type of active materials.

[0034] In order to meet people's demand for high energy density of electrochemical devices such as lithium-ion batteries, the voltage platform of lithium-ion batteries needs to be repeatedly improved. However, as the voltage increases, the side reactions between the positive electrode material and the electrolyte become more serious, and the surface of the positive electrode material particles will undergo phase change and deactivation, resulting in increased impedance and capacity loss. In addition, the electrolyte will oxidize on the surface of the positive electrode material to form byproducts and adhere to the surface of the positive electrode material, further leading to increased impedance and rapid decay of the positive electrode material capacity. Therefore, it is crucial to improve the stability of the positive electrode material or the surface of the positive electrode material.

[0035] In the prior art, in order to improve the cycle performance and safety performance of the positive electrode material under high voltage, the surface stability of the positive electrode material is usually improved by coating or doping the surface of the positive electrode material. For example, when modifying lithium cobalt oxide, a commonly used positive electrode material in the prior art, other metal elements are usually introduced to replace the cobalt element in lithium cobalt oxide, or other non-metallic elements are introduced to replace the oxygen element in lithium cobalt oxide to stabilize the bulk structure of lithium cobalt oxide. For another example, the prior art will also form a stable coating layer on the surface of the synthesized lithium cobalt oxide to reduce or isolate the side reactions between lithium cobalt oxide and the electrolyte and extend the cycle life of the material. However, the above-mentioned improvement methods still have certain defects to a greater or lesser extent, such as requiring more complicated process operations, increasing process costs, and being unfavorable for industrial production.

[0036] At least to overcome the above-mentioned defects existing in the prior art, the present application further studies the surface structure of the positive electrode material. The present application ensures the cycle performance of the electrochemical device under high voltage conditions by using a positive electrode material with a specific surface structure, alleviates the problems of poor structural stability and poor electrochemical stability caused by high voltage working conditions, thereby improving the cycle performance of the electrochemical device. The positive electrode material with a special surface structure of the present application can be achieved by using an in-situ generated rock salt phase layer with a specific ratio and structure of rock salt phase-pores, so that it will not fail during high voltage applications.

[0037] In some embodiments of the present application, an electrochemical device is provided, which includes a positive electrode, a negative electrode and an electrolyte as described below.

[0038] [positive electrode]

[0039] According to some embodiments of the present application, a positive electrode is provided, which includes: a positive electrode current collector and a positive electrode active material layer arranged on one or both surfaces of the positive electrode current collector. The positive electrode active material layer can be one or more layers, and each layer of the multiple layers of positive electrode active material layers can contain the same or different positive electrode materials. Among them, the positive electrode material includes a positive electrode active material. Taking the electrochemical device as a lithium ion battery as an example, the positive electrode active material is any substance that can reversibly embed and de-embed metal ions such as lithium ions.

[0040] According to some embodiments of the present application, there is no particular limitation on the type of positive electrode current collector, and a known current collector can be used. Examples of positive electrode current collectors include, but are not limited to, metal materials such as aluminum, nickel, and nickel-plated steel. In some embodiments, the positive electrode current collector is aluminum.

[0041] In some embodiments, the positive electrode material of the present application is characterized in that it includes: a substrate; and a surface portion covering at least a portion of the surface of the substrate, the surface portion including a rock salt phase layer; wherein the mass percentage of oxygen element in the rock salt phase layer is W1, the mass percentage of oxygen element in the substrate is W2, and the ratio of W1 to W2, W1 / W2, is 0.15 to 0.65.

[0042] According to some embodiments of the present application, oxygen is introduced into the matrix and the rock salt phase layer of the positive electrode material at the same time, and the ratio of the mass percentage of oxygen in the rock salt phase layer to the mass percentage of oxygen in the matrix is ​​in the range of 0.15 to 0.65, and any point value in the range or any sub-interval in the range, all belong to the protection scope of the present application. Preferably, in some embodiments, the ratio of the mass percentage of oxygen in the rock salt phase layer to the mass percentage of oxygen in the matrix is ​​in the range of 0.19 to 0.60. Typically but not limiting, the ratio of the mass percentage of oxygen in the rock salt phase layer to the mass percentage of oxygen in the matrix is, for example, about 0.15, about 0.16, about 0.19, about 0.2, about 0.3, about 0.35, about 0.4, about 0.45, about 0.5, about 0.55, about 0.6, about 0.65, and the range formed by any two of these point values ​​and any value in the range.

[0043] Adjusting and optimizing the ratio of W1 to W2 helps to improve the electrochemical properties of the positive electrode material, especially the cycle performance. Specifically, the rock salt phase salt layer mainly contains anions such as elemental oxygen and fluorine, while the anions inside the matrix are mainly oxygen. When oxygen and transition metals are covalently bonded to form a framework structure, oxygen can fix the transition metal to form a channel to ensure lithium ion transmission. When the ratio of W1 to W2 is less than 0.15, the oxygen content of the rock salt phase layer is too low, the oxygen defect concentration is too high, the oxygen structure is prone to instability, and the oxygen in the structure can assist lithium ion transmission. Too little oxygen is not conducive to ion transmission and will deteriorate the cycle performance. When the ratio of W1 to W2 is greater than 0.65, there are more oxygen-rich structures in the rock salt layer, which are easy to form a large number of side reactions with the electrolyte, causing the rock salt phase layer and the interface layer to become unstable, and also deteriorating the cycle performance.

[0044] In some embodiments, the rock salt phase layer includes a rock salt phase and holes, and in the orthographic projection in the observation direction, the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is 0.01 to 0.7.

[0045] The term "ratio of the projected area of ​​holes to the projected area of ​​rock salt phase" refers to the value obtained by comparing the projected area of ​​holes to the projected area of ​​rock salt phase in the observation direction. In some embodiments, the observation area of ​​the rock salt phase layer contains both rock salt phase and holes, and in the observation area, the proportion of the projected area of ​​the rock salt phase in the observation direction is greater than the proportion of the projected area of ​​the holes, especially the value obtained by comparing the projected area of ​​the holes to the projected area of ​​the rock salt phase is in the range of 0.01 to 0.7.

[0046] The surface of the positive electrode material is at least partially covered with a rock salt phase layer in which a rock salt phase and pores coexist. This rock salt phase-pore structure has a strong ability to limit oxygen dissolution, and can block the invasion of electrolyte, increase the structural stability of the positive electrode material, and have improved cycle performance under high voltage. In detail, the rock salt phase structure is generated in situ during the high voltage cycle process, so it is more tightly combined with the material, and the pore structure is formed after rearrangement by the numerous oxygen vacancies formed by the oxygen precipitated in the early stage of the cycle. In general, the rock salt phase structure itself is dense and non-ion-conductive, and the dense rock salt phase layer will cause the conductivity of the material to drop rapidly and fail. The rock salt phase-pore structure obtained by this rearrangement is itself a non-dense layer, so it has ion-conducting ability. In addition, the pore is a softer structure in this structure, and the rock salt phase is a relatively rigid structure. This soft and rigid composite structure is conducive to the release of stress, thereby maintaining the stability of the structure during the cycle.

[0047] In addition, it is also worth noting that the surface rock salt phase and holes of the rock salt phase layer coexist, and the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase in the observation direction is 0.01 to 0.7, and any point value within the range or any sub-interval within the range, all belong to the protection scope of the present application. Preferably, in some embodiments, the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is about 0.2 to about 0.7. More preferably, in some embodiments, the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is about 0.3 to about 0.6. Typically but not restrictively, the ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is, for example, about 0.01, about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, and the range formed by any two of these point values ​​and any value in the range.

[0048] The appropriate ratio of the projected area of ​​the pores to the rock salt phase makes the density of the rock salt phase layer appropriate, which helps to improve the ion conductivity of the rock salt phase layer. The improvement of the ion conductivity of the positive electrode material can effectively improve the positive electrode material's ability to conduct lithium ions and reduce the impedance of the positive electrode material. In addition, this rock salt phase layer with appropriate density is conducive to the release of stress and can effectively resist the erosion of the electrolyte, so that during the cycle process, the positive electrode material described in this application exhibits excellent structural stability and cycle performance under high voltage charge and discharge conditions.

[0049] In some embodiments, both the rock salt phase layer and the matrix contain element TM; the mass percentage of TM element in the rock salt phase layer is T1, the mass percentage of TM element in the matrix is ​​T2, and the ratio of T1 to T2 is 0.15 to 0.5, wherein the element TM includes at least one of Co, Mn or Ni.

[0050] According to some embodiments of the present application, the element TM is simultaneously introduced into the matrix and the rock salt phase of the positive electrode material. For example, the element TM can be Co, Mn, Ni, Co and Mn, Co and Ni, Ni and Mn, Co, Mn and Ni, and in particular, the element TM can be Co. In this way, by simultaneously introducing the element TM into the matrix and the rock salt phase, the matrix and the rock salt phase can have better compatibility, promote the solid solution between the matrix and the rock salt phase, thereby strengthening the association between the matrix and the rock salt phase, making the rock salt phase more strongly attached to the surface of the matrix, and stabilizing the surface structure of the positive electrode material and improving the interface properties of the positive electrode material. In addition, it also helps to construct an effective lithium ion channel and promote the transmission and diffusion of lithium ions.

[0051] The ratio of the mass percentage of the TM element in the rock salt phase layer to the mass percentage of the TM element in the matrix is ​​in the range of 0.15 to 0.5, and can further be in the range of 0.19 to 0.49. Typically but not limiting, the ratio of the mass percentage of the TM element in the rock salt phase layer to the mass percentage of the TM element in the matrix is, for example, about 0.15, about 0.16, about 0.19, about 0.2, about 0.3, about 0.35, about 0.4, about 0.45, about 0.48, about 0.49, about 0.5, and any range formed by any two of these point values ​​and any value in the range.

[0052] Adjusting and optimizing the ratio of T1 to T2 helps to improve the electrochemical performance of the positive electrode material. Specifically, the element TM in the rock salt phase layer can be introduced during synthesis or migrated out internally during the cycle process. The rock salt phase layer can isolate the contact between the electrolyte and the matrix, reducing the migration of the element TM. The element TM in the rock salt phase layer can ensure the electron transport of the rock salt phase layer. When the ratio of T1 to T2 is less than 0.15, the element TM content in the rock salt phase layer is low, which reduces the electron transportability and reduces the cycle performance. When the ratio of T1 to T2 is greater than 0.5, the element TM content in the rock salt phase layer is high, which will cause the TM in the rock salt phase layer to continue to react with the electrolyte and overflow, reducing its role as a protective layer.

[0053] In some embodiments, the thickness of the rock salt phase layer is 20nm to 200nm. In some embodiments, the thickness of the rock salt phase layer is 30nm to 180nm. In some embodiments, the thickness of the rock salt phase layer is 40nm to 150nm. Typically but not limiting, the thickness of the rock salt phase layer can be, for example, about 20nm, about 30nm, about 40nm, about 50nm, about 60nm, about 80nm, about 100nm, about 120nm, about 150nm, about 180nm, about 200nm, and any range formed by any two of these point values ​​and any value in the range.

[0054] In some embodiments, the rock salt phase layer contains element A, A includes but is not limited to at least one of F, N or Na, and the electrolyte contains element A.

[0055] According to some embodiments of the present application, element A is introduced into the rock salt phase and the electrolyte of the positive electrode material at the same time. For example, element A can be F, N, Na, F and N, F and Na, N and Na, or F, N and Na. In this way, during the electrochemical application process, the rock salt phase layer has a stronger affinity with the electrolyte, which reduces the further transformation of the surface rock salt layer structure caused by side reactions and the generation of by-products at the interface. In addition, element A can be dynamically transmitted between the rock salt phase layer and the electrolyte, so that the surface structure can better adapt to the ion transmission of the system.

[0056] The difference between the mass percentage of element A in the rock salt phase layer and the mass percentage of element A in the electrolyte is no more than 10%, that is, |the difference between the mass percentage of element A in the rock salt phase layer and the mass percentage of element A in the electrolyte|≤10%. The mass percentage of element A in the rock salt phase layer can be obtained by EDS testing.

[0057] In some embodiments, the rock salt phase includes M x A y O m, wherein M includes at least one of Co, Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn or Cr, A includes at least one of F, N or Na, 1≤x≤6, 1≤y≤4, 0.5x≤m≤2x+y. Preferably, according to some embodiments of the present application, M includes at least one of Co, Mn, Ni, Ti, Al and Mg. It should be understood that the element M in the rock salt phase includes at least the same type of the above-mentioned element TM as that contained in the matrix material, that is, the element M includes at least one of Co, Mn or Ni.

[0058] In some embodiments, the composition of the rock salt phase may be Al x1 Co x2 F y O m , where 1≤x1+x2≤6, 1≤y≤4, 0.5(x1+x2)≤m≤2(x1+x2)+y.

[0059] In some embodiments, the composition of the rock salt phase may be Al x1 Co x2 Ti x3 F y O m , or Al x1 Co x2 Ni x3 F y O m , or Ni x1 Mn x2 Co x3 F y O m , among which, 1≤x1+x2+x3≤6, 1≤y≤4, 0.5(x1+x2+x3)≤m≤2(x1+x2+x3)+y.

[0060] In some embodiments, the composition of the rock salt phase may be Al x1 Mg x2 Ti x3 Co x4 F y O m , among which, 1≤x1+x2+x3+x4≤6, 1≤y≤4, 0.5(x1+x2+x3+x4)≤m≤2(x1+x2+x3+x4)+y.

[0061] In some embodiments, the composition of the rock salt phase may be Al x1 Co x2 Na y1 F y2 O m, where 1 ≤ x1 + x2 ≤ 6, 1 ≤ y1 + y2 ≤ 4, and 0.5(x1 + x2) ≤ m ≤ 2(x1 + x2) + (y1 + y2).

[0062] This application does not impose special restrictions on the specific type of the matrix. Any cathode active material that can exhibit electrochemical activity (such as being able to reversibly intercalate or deintercalate lithium ions) belongs to the protection scope of this application. For example, the matrix may include, but is not limited to, lithium-containing transition metal composite oxides. For example, the lithium-containing transition metal composite oxide may be a lithium-containing transition metal composite oxide containing cobalt (Co) element.

[0063] In some embodiments, the matrix includes ternary materials. Preferably, according to some embodiments of this application, the ternary materials include one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, doped and modified lithium nickel cobalt manganese oxide, or doped and modified lithium nickel cobalt aluminate.

[0064] In some embodiments, the matrix includes lithium transition metal composite oxides. Exemplarily, the lithium metal composite oxide may be lithium cobalt oxide or doped and modified lithium cobalt oxide.

[0065] In some embodiments, the composition of the lithium transition metal composite oxide can be expressed as Li a Me b Co c O d-e T e , where Me includes at least one of Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn, Zr, or Cr, T is a halogen, 0.2 ≤ a ≤ 1.2, 0 ≤ b ≤ 1, 0 < c ≤ 1, 1 ≤ d ≤ 2, 0 ≤ e ≤ 1. Preferably, according to some embodiments of this application, Me includes at least one of Mn, Ni, Ti, Al, and Mg.

[0066] In some embodiments, the composition of the lithium transition metal composite oxide is Li a Ni b1 Mn b2 Co c O d-e T e , where 0.8 ≤ a ≤ 1.2, 0 ≤ b1 + b2 ≤ 1, 0 < c ≤ 1, and there are no special restrictions on the specific value ranges of b1 and b2. For example, 0 ≤ b1 < 1 and 0 ≤ b2 < 1. Preferably, according to some embodiments of this application, the composition of the lithium metal composite oxide includes LiCoO 2 , LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 , LiNi 0.5 Mn 0.3Co 0.2 O 2 、LiNi 0.8 Mn 0.1 Co 0.1 O 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 At least one of .

[0067] In some embodiments, the lithium metal composite oxide comprises Li a Al b3 Mg b4 Ti b5 Co c O d-e T e , wherein 0≤b3+b4+b5≤1, and there is no special restriction on the specific value range of b3, b4, and b5, for example, 0≤b3<1, 0≤b4<1, and 0≤b5<1. Preferably, according to some embodiments of the present application, the composition of the lithium metal composite oxide includes LiAl 0.01 Co 0.99 O 2 、LiAl 0.01 Mg 0.01 Ti 0.01 Co 0.97 O 2 、LiMg 0.05 Co 0.95 O 2 At least one of .

[0068] In some embodiments, the positive electrode material further comprises a binder, and optionally further comprises a positive electrode conductive material.

[0069] The binder improves the bonding of the positive electrode active material particles to each other and also improves the bonding of the positive electrode active material to the current collector. Non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0070] In some embodiments, the positive electrode material also includes a positive electrode conductive material, thereby giving the electrode conductivity. The positive electrode conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of positive electrode conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0071] Based on the above characteristics of the cathode material of the present application, it can be known that the cathode material has excellent structural stability. When the cathode material described in the present application is applied to an electrochemical device (eg, a lithium-ion battery), the electrochemical device can exhibit excellent electrochemical performance, especially good cycle performance.

[0072] The embodiments of the present application also provide a method for preparing the positive electrode material involved in the above embodiments. The preparation method is simple and easy to implement, has a wide range of raw material sources, and is easy to control reaction conditions, and is suitable for industrial production.

[0073] In some embodiments, the positive electrode material is prepared by a solid phase sintering coating method. In other embodiments, the positive electrode material is prepared by a solid phase sintering combined with an electrochemical reaction.

[0074] Exemplarily, taking lithium cobalt oxide as the matrix material, a rock salt phase layer is formed on the surface of the lithium cobalt oxide by a solid phase sintering coating method to obtain a positive electrode material of lithium cobalt oxide coated with a rock salt phase layer having a rock salt phase-pore structure. However, it should be understood that the matrix material is not limited to lithium cobalt oxide. When other types of matrix materials are used, the positive electrode material can also be prepared by the same or similar method. Specifically, the solid phase sintering coating can include the following steps:

[0075] (1) Mix lithium carbonate and cobalt tetroxide in a certain proportion.

[0076] (2) Stir the mixture from step (1) for about 6 h to about 24 h until the mixture is evenly mixed.

[0077] (3) The powder obtained in step (2) is subjected to high temperature treatment, ground, and sieved to obtain lithium cobalt oxide.

[0078] (4) Add the following substances in sequence to the lithium cobalt oxide obtained in step (3): a compound containing element M, such as a Co compound, such as CoO, CoCl 2 、Co 2 O 3 etc.; compounds containing element A, such as compounds containing F, such as NH 4 F, etc.; additives such as KClO 3, oxalic acid, NH 4 HCO 3 Preferably, CoCl2, NH4F and NH 4 HCO 3 , its (CoCl 2 NH 4 F and NH 4 HCO 3 ) has a total mass of about 0.3% to about 5% of the mass of lithium cobalt oxide, wherein the mass of the cobalt element is less than about 40%, and the mass of the additive is not less than about 5%.

[0079] (5) Stir the mixture from step (4) for about 6 h to about 12 h until the mixture is homogeneous.

[0080] (6) The mixture obtained in (5) is subjected to high temperature treatment, ground, and sieved to obtain a lithium cobalt oxide positive electrode material having a rock salt phase layer with a rock salt phase-pore structure.

[0081] In some embodiments, in step (1), the molar ratio of lithium carbonate to cobalt oxide is about 0.9 to about 1.1.

[0082] In some embodiments, in steps (1), (2) and (5), the powders are mixed uniformly without obvious agglomeration and separation. There is no particular limitation on the specific mixing method, for example, the mixing can be performed using, but not limited to, any of a ball mill, a V-type mixer, a three-dimensional mixer, an air flow mixer, and a horizontal mixer.

[0083] In some embodiments, in step (3), the sintering temperature ranges from about 500° C. to about 1100° C., and the sintering time ranges from about 12 h to about 72 h.

[0084] In some embodiments, the sintering atmosphere is an air atmosphere or an inert atmosphere.

[0085] In some embodiments, in steps (3) and (6), the sieving standard is about 100 to about 500 mesh.

[0086] In some embodiments, the treatment temperature is related to the substance added in (4), the temperature range is about 300 to about 1000° C., preferably about 500° C., and the reaction time is about 4 to about 24 hours, preferably about 8 hours.

[0087] In some embodiments, in step (4), the added compound containing element M may be a Co-containing compound, but is not limited to a Co-containing compound. For example, it may also be a Ni-containing compound, Mn-containing compound, or other suitable precursor substitutions or mixtures. The added compound containing element A may be a F-containing compound, but is not limited to a F-containing compound. For example, it may also be a Na-containing compound, N-containing compound, or other suitable compounds or mixtures.

[0088] In other embodiments, taking lithium cobalt oxide as the matrix material, a rock salt phase layer is formed on the surface of the lithium cobalt oxide by solid phase sintering combined with an electrochemical reaction to obtain a positive electrode material having a rock salt phase-pore structure and a rock salt phase layer coated with lithium cobalt oxide. However, it should be understood that the matrix material is not limited to lithium cobalt oxide, and when other types of matrix materials are used, the positive electrode material can also be prepared by the same or similar method. Specifically, the method of solid phase sintering combined with an electrochemical reaction can include the following steps:

[0089] (a) A matrix material such as lithium cobalt oxide material is obtained by solid phase sintering reaction.

[0090] (b) subjecting the lithium cobalt oxide material obtained in step (a) to a secondary sintering reaction to modify the surface.

[0091] (c) assembling the lithium cobalt oxide material obtained in step (b) to form a battery, wherein the electrolyte in the battery comprises element A, A comprises at least one of F, N or Na, and the content of element A in the rock salt phase differs from the content of element A in the electrolyte by no more than about 10%. For example, the electrolyte comprises EC+DMC+PC+VC=1:1:1:1, and 1 molLiPF 6 , and add LiPF 6 About 0.1% NaPF by mass 6 . And charge at a current density of 10mA / g, charge to X1 V as the cut-off voltage, and keep constant voltage charging at X1 until the current is less than s uA. After the end of charging, let it stand for about 5 minutes, and discharge with a current of about 5mA / g. After discharging for 1h, change the discharge current to about 50mA / g, discharge to X2 V, and let it stand for about 5 minutes.

[0092] The positive electrode material can be obtained by cycling the method described in step (c) for 2 to 5 times.

[0093] In some embodiments, in step (c), X1 is not less than about 4.6 V and not more than about 4.8 V, preferably about 4.7 V. X2 is not more than about 3.5 V and not less than about 2.8 V, preferably about 3.0 V. S is between about 10 and about 70 uA, preferably about 50 uA.

[0094] According to an embodiment of the present application, the positive electrode material needs to form a layer of rock salt phase coating with alternating density on its surface, that is, a positive electrode material with a rock salt phase layer with a rock salt phase-pore structure. The formation of the rock salt phase layer can be modified by using common metal oxides, etc., and an additive with decomposition ability is added to the modified substance. After high temperature reaction, it will decompose so that the surface coating layer of the material forms a structure with alternating density. The amount of decomposable substance added is related to the proportion of loose structure to a certain extent, but it is not an absolute mathematical proportional relationship. In addition, the positive electrode material can obtain the rock salt phase layer of the characteristics by the above-mentioned method of solid phase sintering combined with electrochemical reaction, and the method of solid phase sintering combined with electrochemical reaction is only one of the methods, and it is not necessarily applicable to all systems. The principle is that by controlling the conditions such as the charging cut-off voltage and current density, the original coating layer, the near-surface layer of the material, etc. react and reorganize, thereby forming a structure with alternating density.

[0095] [negative electrode]

[0096] In some embodiments of the present application, the negative electrode includes: a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0097] According to some embodiments of the present application, the negative electrode active material layer includes a negative electrode active material. There is no particular limitation on the specific type of the negative electrode active material, which can be selected according to needs.

[0098] In some embodiments, the negative electrode active material may be a negative electrode active material capable of absorbing / releasing lithium (Li), including but not limited to carbon materials, silicon-based materials, metal compounds, oxides, sulfides, lithium nitrides such as LiN 3 , lithium metal, metals that form alloys with lithium, and polymer materials.

[0099] In some embodiments, carbon materials may include, but are not limited to, low-graphitization carbon, easily graphitized carbon, artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, organic polymer compound sintered body, carbon fiber and activated carbon. Among them, coke may include pitch coke, needle coke and petroleum coke. Organic polymer compound sintered body refers to a material obtained by calcining a polymer material (e.g., phenol plastic or furan resin) at an appropriate temperature to carbonize it, and these materials can be divided into low-graphitization carbon or easily graphitized carbon. Polymer materials may include, but are not limited to, polyacetylene and polypyrrole.

[0100] Among these negative electrode materials that can absorb / release lithium (Li), further, materials whose charge and discharge voltages are close to those of lithium metal are selected. This is because the lower the charge and discharge voltages of the negative electrode material, the easier it is for the lithium-ion battery to have a higher energy density. Among them, carbon materials can be selected as negative electrode materials because their crystal structures only change slightly during charge and discharge, so good cycle characteristics and large charge and discharge capacities can be obtained. Graphite can be selected in particular because it can give a large electrochemical equivalent and a high energy density.

[0101] In addition, the negative electrode material capable of absorbing / releasing lithium (Li) may include single substance lithium metal, metal elements and semi-metal elements capable of forming alloys with lithium (Li), alloys and compounds of such elements, etc. In particular, they are used together with carbon materials, because in this case, good cycle characteristics and high energy density can be obtained. In addition to alloys including two or more metal elements, the alloys used here also include alloys containing one or more metal elements and one or more semi-metal elements. The alloy may be in the following states: solid solution, eutectic crystal (eutectic mixture), intermetallic compound and mixture thereof. Examples of metal elements and semi-metal elements may include tin (Sn), lead (Pb), aluminum (Al), indium (In), silicon (Si), zinc (Zn), antimony (Sb), bismuth (Bi), cadmium (Cd), magnesium (Mg), boron (B), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), zirconium (Zr), yttrium (Y) and hafnium (Hf).

[0102] In some embodiments, the negative electrode active material may also be selected from silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , one or more of Li-Al alloys.

[0103] In addition, inorganic compounds that do not include lithium (Li), such as MnO, may be used in the negative electrode. 2 、V 2 O 5 、V 6 O 13 , NiS and MoS.

[0104] In some embodiments, the negative active material layer may include a binder and optionally further include a conductive material.

[0105] The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. Non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc.

[0106] The negative electrode active material layer includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0107] As the negative electrode current collector for holding the negative electrode active material, any known current collector can be used. Examples of the negative electrode current collector include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.

[0108] In the case where the negative electrode current collector is a metal material, the negative electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil based on a rolling method or an electrolytic copper foil based on an electrolytic method.

[0109] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector is within the range of any two of the above values.

[0110] [Electrolyte]

[0111] The electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte used in the electrochemical device of the present application further includes an additive.

[0112] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the art as a solvent for the electrolyte.

[0113] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, linear carbonates, cyclic carboxylates, linear carboxylates, cyclic ethers, linear ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0114] In some embodiments, examples of cyclic carbonates may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0115] In some embodiments, examples of linear carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted linear carbonates may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, and 2,2,2-trifluoroethyl methyl carbonate, etc.

[0116] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.

[0117] In some embodiments, examples of chain carboxylates may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate, and ethyl pivalate. In some embodiments, some of the hydrogen atoms of chain carboxylates may be substituted by fluorine. In some embodiments, examples of fluorine-substituted chain carboxylates may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate, and 2,2,2-trifluoroethyl trifluoroacetate.

[0118] In some embodiments, examples of cyclic ethers may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl 1,3-dioxolane, 4-methyl 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.

[0119] In some embodiments, examples of chain ethers may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane, and the like.

[0120] In some embodiments, examples of phosphorus-containing organic solvents may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.

[0121] In some embodiments, examples of sulfur-containing organic solvents may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.

[0122] In some embodiments, the aromatic fluorinated solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0123] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, or ethyl acetate. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0124] After adding chain carboxylic acid esters and / or cyclic carboxylic acid esters to the electrolyte, the chain carboxylic acid esters and / or cyclic carboxylic acid esters can form a passivation film on the electrode surface, thereby improving the capacity retention rate of the electrochemical device after intermittent charging cycles. In some embodiments, the electrolyte contains 1% to 60% of chain carboxylic acid esters, cyclic carboxylic acid esters and combinations thereof. In some embodiments, the electrolyte contains ethyl propionate, propyl propionate, γ-butyrolactone and combinations thereof, and the content of the combination is 1% to 60%, 10% to 60%, 10% to 50%, 20% to 50% based on the total weight of the electrolyte. In some embodiments, the electrolyte contains 1% to 60%, 10% to 60%, 20% to 50%, 20% to 40% or 30% of propyl propionate based on the total weight of the electrolyte.

[0125] In some embodiments, the electrolyte contains additives, and examples of the additives may include, but are not limited to, one or more of the following: fluorocarbonate, ethylene carbonate containing carbon-carbon double bonds, compounds containing sulfur-oxygen double bonds, and acid anhydrides.

[0126] In some embodiments, the additive is present in an amount of 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the total weight of the electrolyte.

[0127] In some embodiments, the additive comprises one or more fluorocarbons. During the charge / discharge of the lithium-ion battery, the fluorocarbons can work together with the propionates to form a stable protective film on the surface of the negative electrode, thereby inhibiting the decomposition reaction of the electrolyte.

[0128] In some embodiments, the fluorinated carbonate has the formula C=O(OR 1 )(OR 2 ), where R 1 and R 2 Each is selected from an alkyl or halogenated alkyl group having 1 to 6 carbon atoms, wherein R 1 and R 2 At least one of them is selected from a fluoroalkyl group having 1 to 6 carbon atoms, and R 1 and R 2 Optionally together with the atoms to which it is attached, it forms a 5- to 7-membered ring.

[0129] In some embodiments, examples of fluorocarbonates may include, but are not limited to, one or more of the following: fluoroethylene carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate, etc.

[0130] In some embodiments, the additive includes one or more ethylene carbonates containing carbon-carbon double bonds. Examples of ethylene carbonates containing carbon-carbon double bonds may include, but are not limited to, one or more of the following: vinyl carbonate, methyl vinyl carbonate, ethyl vinyl carbonate, 1,2-dimethyl vinyl carbonate, 1,2-diethyl vinyl carbonate, fluoro vinyl carbonate, trifluoromethyl vinyl carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-diethyl-2-methylene ethylene carbonate, etc. In some embodiments, ethylene carbonates containing carbon-carbon double bonds include vinyl carbonate, which is easy to obtain and can achieve more excellent effects.

[0131] In some embodiments, the additive comprises one or more compounds containing sulfur-oxygen double bonds. Examples of compounds containing sulfur-oxygen double bonds may include, but are not limited to, one or more of the following: cyclic sulfates, chain sulfates, chain sulfonates, cyclic sulfonates, chain sulfites, and cyclic sulfites, etc.

[0132] In some embodiments, the additive is a combination of fluorocarbonic acid ester and ethylene carbonate containing carbon-carbon double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound containing sulfur-oxygen double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound with 2-4 cyano groups. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic carboxylic acid ester. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic phosphoric acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and sulfonic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid sulfonic acid anhydride.

[0133] According to some embodiments of the present application, the electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of the electrolyte may include, but are not limited to, LiPF 6 , LiBF 4 、LiClO 4 、LiAlF 4 、LiSbF 6 、LiTaF 6 ,LiWF 7 Inorganic lithium salts such as LiWOF 5 Lithium tungstate, etc.; HCO 2 Li, CH 3 CO2 Li, CH 2 FCO 2 Li, CHF 2 CO 2 Li, CF 3 CO 2 Li, CF 3 CH 2 CO 2 Li, CF 3 CF 2 CO 2 Li, CF 3 CF 2 CF 2 CO 2 Li, CF 3 CF 2 CF 2 CF 2 CO 2 Lithium carboxylates such as Li; FSO 3 Li, CH 3 SO 3 Li, CH 2 FSO 3 Li, CHF 2 SO 3 Li, CF 3 SO 3 Li, CF 3 CF 2 SO 3 Li, CF 3 CF 2 CF 2 SO 3 Li, CF 3 CF 2 CF 2 CF 2 SO 3 Lithium sulfonate salts such as Li; LiN(FCO) 2 、LiN(FCO)(FSO 2 )、LiN(FSO 2 ) 2 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiN(CF3 SO 2 )(C 4 F 9 SO 2 ) and other lithium imide salts; LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5 SO 2 ) 3 Methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) lithium phosphate, tetrafluoro(malonate) lithium phosphate; and LiPF 4 (CF 3 ) 2 、LiPF 4 (C 2 F 5 ) 2 、LiPF 4 (CF 3 SO 2 ) 2 、LiPF 4 (C 2 F 5 SO 2 ) 2 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiBF 3 C 3 F 7 , LiBF 2 (CF 3 ) 2 , LiBF 2 (C 2 F 5 ) 2 , LiBF 2 (CF 3 SO 2 ) 2 , LiBF 2 (C 2 F 5 SO 2 ) 2Fluorine-containing organic lithium salts; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato)phosphate, and lithium tris(oxalato)phosphate.

[0134] In some embodiments, the electrolyte is selected from LiPF 6 、LiSbF 6 、LiTaF 6 、FSO 3 Li, CF 3 SO 3 Li、LiN(FSO 2 ) 2 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 、LiPF 3 (CF 3 ) 3 、LiPF 3 (C 2 F 5 ) 3 , lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which help to improve the output power characteristics, high-rate charge and discharge characteristics, high-temperature storage characteristics and cycle characteristics of electrochemical devices.

[0135] The content of the electrolyte is not particularly limited, as long as it does not impair the effect of the present application. Exemplarily, in some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range composed of any two of the above values. When the electrolyte concentration is within the above range, the lithium as a charged particle will not be too little, and the viscosity can be kept in an appropriate range, thereby easily ensuring good conductivity.

[0136] When two or more electrolytes are used, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range of any two of the above values.

[0137] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more salts other than these. As salts other than these, the lithium salts exemplified above can be cited, and in some embodiments, LiPF 6 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 、LiPF 3 (CF 3 ) 3 、LiPF 3 (C 2 F 5 ) 3 In some embodiments, the salt other than LiPF 6 .

[0138] In some embodiments, the content of the other salts is greater than 0.01% or greater than 0.1% based on the total weight of the electrolyte. In some embodiments, the content of the other salts is less than 20%, less than 15%, or less than 10% based on the total weight of the electrolyte. In some embodiments, the content of the other salts is within the range formed by any two of the above values. The other salts having the above content help balance the conductivity and viscosity of the electrolyte.

[0139] In the electrolyte, in addition to the above-mentioned solvents, additives and electrolyte salts, additional additives such as negative electrode film forming agents, positive electrode protective agents, and anti-overcharge agents may be contained as needed. As additives, additives generally used in non-aqueous electrolyte secondary batteries can be used, examples of which may include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, propene sultone, etc. These additives can be used alone or in any combination. In addition, the content of these additives in the electrolyte is not particularly limited, and can be appropriately set according to the type of the additive, etc. In some embodiments, based on the total weight of the electrolyte, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5%.

[0140] [Isolation film]

[0141] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.

[0142] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, glass filters, etc. In some embodiments, the material of the isolation membrane is a glass filter. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0143] The separator may also be a material formed by laminating the above materials, examples of which include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0144] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0145] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.

[0146] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the separator is within the range of any two of the above values. When the thickness of the separator is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0147] When a porous material such as a porous sheet or non-woven fabric is used as a separator, the porosity of the separator is arbitrary. In some embodiments, the porosity of the separator is greater than 20%, greater than 35%, or greater than 45%. In some embodiments, the porosity of the separator is less than 90%, less than 85%, or less than 75%. In some embodiments, the porosity of the separator is within the range formed by any two of the above values. When the porosity of the separator is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good rate characteristics.

[0148] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range formed by any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the membrane resistance can be suppressed while preventing short circuit, so that the electrochemical device has good rate characteristics.

[0149] [Electrochemical device]

[0150] The electrochemical device includes an electrode group, a current collecting structure, an outer casing and a protective element.

[0151] Electrode Group

[0152] The electrode group may be any one of a laminated structure formed by laminating the above-mentioned positive electrode and the negative electrode with the above-mentioned separator interposed therebetween, and a structure formed by spirally winding the above-mentioned positive electrode and the negative electrode with the above-mentioned separator interposed therebetween. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range formed by any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction in characteristics such as repeated charge and discharge performance and high temperature storage associated with the increase in internal pressure can be suppressed, thereby preventing the gas release valve from operating.

[0153] Current collection structure

[0154] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.

[0155] External shell

[0156] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.

[0157] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.

[0158] Protection components

[0159] The protection element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is released or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat is released. The above protection element may be selected to be an element that does not work in normal use of high current, or may be designed in a form that does not cause abnormal heat release or thermal runaway even if the protection element is not present.

[0160] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0161] In some embodiments of the present application, taking a lithium-ion secondary battery as an example, the positive electrode, the separator, and the negative electrode are wound or stacked in order to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion secondary battery. Then, the prepared lithium-ion secondary battery is subjected to performance testing and cycle testing. Those skilled in the art will appreciate that the preparation method of the electrochemical device (e.g., lithium-ion battery) described above is only an embodiment. Without departing from the contents disclosed in the present application, other methods commonly used in the art may be used.

[0162] [Electronic equipment]

[0163] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0164] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0165] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0166] Example

[0167] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0168] 1. Preparation of lithium-ion batteries

[0169] 1. Preparation of positive electrode

[0170] The positive electrode material, conductive material (Super-P) and polyvinylidene fluoride (PVDF) prepared in the following examples and comparative examples were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3%, and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12μm aluminum foil, dried, cold pressed, and then cut into pieces and welded to the pole ears to obtain a positive electrode.

[0171] 2. Preparation of negative electrode

[0172] Graphite, sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) are mixed in a proper amount of deionized water solvent at a weight ratio of 97.5:1.5:1 to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil and dried at 85°C. Then, the negative electrode active material layer is obtained by trimming, cutting, stripping and drying, and then the negative electrode is obtained by cutting and welding the pole ears.

[0173] 3. Preparation of electrolyte

[0174] In a dry argon environment, EC, DMC, PC, and VC (weight ratio 1:1:1:0.01) were mixed and LiPF 6 Mix well to form a basic electrolyte, in which LiPF 6 The concentration is 1 mol / L.

[0175] 4. Preparation of isolation membrane

[0176] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0177] 5. Preparation of lithium-ion batteries

[0178] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.

[0179] The specific implementation of the positive electrode material provided in the present application will be described in detail below.

[0180] The preparation method of the positive electrode material in Example 1 is as follows: lithium carbonate and cobalt oxide are mixed in a ratio of lithium to cobalt of 1.05, mixed evenly, reacted at 1000°C for 12 hours, ground and sieved to obtain a base material of lithium cobalt oxide. Then, a coating AlF4 is added to the base material of lithium cobalt oxide in an amount not exceeding 1% by mass of the lithium cobalt oxide. 3 , CoF 2 and TiO 2 , and satisfy the molar ratio of Al:Co:Ti=4:1:1, add 30% of the coating mass of NH 4 F and oxalic acid, NH 4The mass of F and oxalic acid is equal. After being fully mixed, the mixture is reacted at 500°C for 12 hours, and then ground and sieved to obtain the positive electrode material.

[0181] The preparation method of the positive electrode material in Example 2 is as follows: lithium carbonate and cobalt oxide are mixed in a lithium-cobalt molar ratio of 1.05, and aluminum oxide with a molar ratio of Al:Co=0.01:0.99 is added, mixed evenly, reacted at 1000°C for 12 hours, ground and sieved to obtain a base material. Then, 0.6% of the base material mass of the coating CoCl 2 、Al 2 O 3 and sodium oxalate, and satisfying the molar ratio of Al:Co:Na=1:1:1, add a mixture of ammonium oxalate and ammonium fluoride in an equal mass ratio, which is 30% of the mass of the coating, and react at 500°C for 8h after being fully mixed, and then grind and sieve to obtain the positive electrode material.

[0182] The preparation method of the positive electrode material in Example 3 is: lithium carbonate and cobalt tetroxide are mixed in a ratio of lithium to cobalt of 1.06, and the oxides of aluminum, magnesium and titanium are added. 2 O 3 , MgO and TiO 2 , with a molar ratio of Co:Al:Mg:Ti=0.97:0.01:0.01:0.01, mixed evenly, reacted at 950°C for 18h, ground and sieved to obtain a matrix material. Then, a coating AlF 3 MgF 2 、TiO 2 and CoF 2 , and satisfy the molar ratio of Al:Mg:Ti:Co=2:1:1:10, add 45% of the weight of the coating material and a mixture of ammonium fluoride and ammonium oxalate in equal weight ratio. After fully mixing, react at 600°C for 6h, and then grind and sieve to obtain the positive electrode material.

[0183] The preparation method of the positive electrode material in Example 4 is as follows: lithium carbonate and cobalt oxide are mixed in a ratio of lithium to cobalt of 1.045, mixed evenly, reacted at 1000°C for 12 hours, ground and sieved to obtain a matrix material. The obtained matrix material is assembled to obtain a battery, and the electrolyte is EC+DMC+PC+VC=1:1:1:0.01, with 2% 2-Cl-sodium benzenesulfonate and 1% succinonitrile relative to the mass of EC, 1mol / L LiPF 6The anode is graphite. It is charged to 4.7V at a current density of 10mA / g, and charged at a constant voltage until the current is less than 50uA. Then it is left to stand for 5min, discharged at a current density of 5mA / g for 1h, and then discharged at a current density of 50mA / g to 3.0V, and left to stand for 5min. This cycle is repeated 3 times to obtain the positive electrode material.

[0184] The preparation method of the positive electrode material in Example 5 is: Ni 0.5 Mn 0.3 Co 0.2 (OH) 2 The mixture was mixed with lithium carbonate in a molar ratio of (Ni+Mn+Co) to Li element of 1:1.05, and reacted at 600°C for 24 hours in an oxygen atmosphere, and then ground and sieved to obtain a matrix material. Then NiF with a molar ratio of Ni:Mn:Co=1.5:1:0.1 was added to the matrix material. 2 、MnF 2 and Co 2 O 3 The mixture A is prepared, and a mixed salt of ammonium bicarbonate and ammonium fluoride in an equal mass ratio of 40% of the mass ratio of the mixture A is added. After being fully stirred, the mixture is reacted at 450° C. for 8 hours, and then ground and sieved to obtain a positive electrode material.

[0185] The difference between Example 6 and Example 5 is that: a coating Al is added to the base material lithium cobalt oxide in an amount not exceeding 1% by mass of the lithium cobalt oxide. 2 O 3 and CoF 2 , and the molar ratio of Al:Co=2:1, 40% of the mass of the coating material NaF is added. The rest is the same as Example 1.

[0186] The difference between Example 7 and Example 1 is that the coating AlF4 is added to the base material lithium cobalt oxide in an amount not exceeding 1% by mass of the lithium cobalt oxide. 3 , CoF 2 and Ni(OH) 2 , and satisfy the molar ratio of Al:Co:Ni=1:2:5, and add a mixture of NaF and sodium bicarbonate in an equal mass ratio, which is 50% of the mass of the coating. The rest is the same as in Example 1.

[0187] The difference between Example 8 and Example 1 is that 30% of the mass of the coating material NaF and sodium oxalate are added, and the masses of NaF and sodium oxalate are equal.

[0188] The difference between Example 9 and Example 5 is that 5% by mass of NaSCN and 10% by mass of NH 4 Cl.

[0189] Comparative Example 1

[0190] Lithium carbonate and cobalt oxide were mixed at a lithium-to-cobalt molar ratio of 1.03, and magnesium element equivalent to 0.05% of the mass of cobalt element was added. They were reacted at 900° C. for 24 hours, ground and sieved to obtain a positive electrode material.

[0191] Comparative Example 2

[0192] Lithium carbonate and cobalt oxide were mixed in a lithium-cobalt molar ratio of 1.05, reacted at 950°C for 18 hours, and ground and sieved. Then, titanium oxide (0.02% by mass of lithium cobalt oxide) and ammonium fluoride (0.005% by mass of lithium cobalt oxide) were added, stirred well, reacted at 750°C for 8 hours, and ground and sieved to obtain a positive electrode material.

[0193] Comparative Example 3

[0194] Lithium carbonate and cobalt oxide were mixed in a lithium-cobalt molar ratio of 1.00, reacted at 950°C for 18 hours, and ground and sieved. Alumina and ammonium oxalate with a mass percentage of 0.02% of lithium cobalt oxide were then added, stirred well, reacted at 750°C for 8 hours, and ground and sieved to obtain a positive electrode material.

[0195] Comparative Example 4

[0196] Ni 0.5 Mn 0.3 Co 0.2 (OH) 2 The mixture is mixed with lithium carbonate in a molar ratio of (Ni+Mn+Co) to Li element of 1:1.05, reacted at 600°C for 24 hours in an oxygen atmosphere, and ground and sieved to obtain a positive electrode material.

[0197] Comparative Example 5

[0198] Lithium carbonate and cobalt oxide were mixed in a lithium-cobalt molar ratio of 1.05, and after mixing them evenly, they were reacted at 1000°C for 12 hours, and then ground and sieved. Then, AlF 3 and Co 2 O 3 , and satisfy the molar ratio of Al:Co=1:1. After fully mixing, react at 500℃ for 12h, grind and sieve to obtain the positive electrode material.

[0199] The specific positive electrode material compositions of Examples 1 to 9 and Comparative Examples 1 to 5 are shown in Table 1 below.

[0200] The determination methods of various performance parameters of the embodiments and comparative examples are as follows.

[0201] 2. Test Method

[0202] 1. Element analysis of positive electrode materials

[0203] The soft pack battery is at 10-30mA / cm 2 The cathode sheet was obtained by fully discharging the cathode sheet in a glove box after standing for 10 min at a current density of 100 V or less. If the cathode sheet is a powder material, it can be used directly.

[0204] The positive electrode sheet is transferred to the FEI Vion Plasma FIB chamber and processed to obtain a sample that can be used for STEM analysis. The sample surface is required to be protected with Pt and processed with a Ga ion beam. The sample thickness does not exceed 100nm; and it is cleaned in low voltage mode to remove the residual surface of the sample processing.

[0205] Observe the sample under a FEI Titan3 G260-300 transmission electron microscope or a similar electron microscope, and collect data using EDS at an appropriate magnification to obtain the element content on the surface and near the surface of the material.

[0206] Collect data from at least 3 different locations and take the average value.

[0207] 2. Rock salt-pore analysis

[0208] In the process of elemental analysis of the cathode material in the above method 1, the surface of the material is photographed in a STEM electron microscope to obtain a structural image with a suitable magnification. The required shooting mode is HAADF.

[0209] The photographs were imported into Image J, and grayscale analysis was used to obtain a three-dimensional grayscale distribution map. In the grayscale distribution map, the area with a grayscale greater than 50% of the maximum value was recorded as the projection area of ​​the rock salt phase, and the area below 50% was recorded as the projection area of ​​the pores.

[0210] 3. Electrochemical cycle test

[0211] At 25°C, the lithium-ion battery was charged to 4.6V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.6V, and then discharged to 3.0V at a constant current of 0.5C. The discharge capacity was recorded as D0. According to the above conditions, the lithium-ion battery was subjected to multiple cycles of "0.5C charge-0.5C discharge" for 50 cycles, and the discharge capacity of the 50th cycle was tested as D.

[0212] The capacity retention rate after room temperature cycling is calculated according to the following formula:

[0213] Capacity retention rate after 50 cycles at 25°C (%) = D / D0×100%.

[0214] 3. Test Results

[0215] The performance tests were carried out on the positive electrode materials and lithium ion batteries in Examples 1 to 9 and Comparative Examples 1 to 5, and the test results are shown in Tables 1 and 2 below, respectively.

[0216] Table 1

[0217]

[0218]

[0219] It can be seen from the data in Table 1 that the capacity retention rate of Examples 1-7 of the positive electrode material having a rock salt phase layer at high voltage is greatly improved compared to Comparative Example 1 without a rock salt phase layer, and has good high-voltage cycle performance. Examples 1-7 in which the ratio of the oxygen content in the rock salt phase layer to the oxygen content in the matrix (W1 / W2) is between 0.15 and 0.65 have better cycle stability than Comparative Examples 2 and 3 in which W1 / W2 is 0.79 and 0.78. Examples 1-7 in which the ratio of the TM content in the rock salt phase layer to the TM content in the matrix (T1 / T2) is between 0.15 and 0.5 have better cycle stability than Comparative Example 2 in which T1 / T2 is 0.61.

[0220] In addition, Examples 1-5 and 7, in which the projected area ratio of the pores to the rock salt phase is 0.01 to 0.7, have better cycle stability than Example 6, in which the projected area ratio of the pores to the rock salt phase is 0. This is because the composite structure of the pores and the rock salt phase is conducive to the release of stress, thereby maintaining the stability of the structure during the cycle.

[0221] Table 2

[0222]

[0223] It can be seen from the data in Table 2 that Examples 1, 5, 8-9, in which the difference between the mass percentage of element A in the rock salt phase and the mass percentage of element A in the electrolyte does not exceed 10%, have better cycle stability than Comparative Examples 4-5 in which the content difference exceeds 10%.

[0224] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0225] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises: a substrate; and A surface layer covering at least a portion of the surface of the substrate, wherein the surface layer includes a rock salt phase layer; The rock salt phase layer includes a rock salt phase and holes. In the forward projection in the observation direction, the ratio of the projection area of ​​the holes to the projection area of ​​the rock salt phase is 0.01 to 0.

7.

2. The positive electrode material according to claim 1, characterized in that The ratio of the projected area of ​​the holes to the projected area of ​​the rock salt phase is 0.2 to 0.

7.

3. The positive electrode material according to claim 1, characterized in that The rock salt phase layer and the matrix both contain element TM; The mass percentage of TM element in the rock salt phase layer is T1, the mass percentage of TM element in the matrix is ​​T2, the ratio of T1 to T2 is 0.15-0.5, wherein the element TM includes at least one of Co, Mn or Ni.

4. The positive electrode material according to claim 3, characterized in that The mass percentage of oxygen element in the rock salt phase layer is W1, the mass percentage of oxygen element in the matrix is ​​W2, and the ratio of W1 to W2 (W1 / W2) is 0.15-0.65; the mass percentage of oxygen element W1 in the rock salt phase layer and the mass percentage of oxygen element W2 in the matrix are obtained by testing using an energy spectrometer under a transmission electron microscope.

5. The positive electrode material according to claim 1, characterized in that The thickness of the rock salt phase layer is 20 nm to 200 nm.

6. The positive electrode material according to claim 1, characterized in that The rock salt phase layer contains element A, and the A includes at least one of F, N or Na.

7. The positive electrode material according to claim 1, characterized in that The rock salt phase layer includes M x A y O m , wherein M includes at least one of Co, Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn or Cr, A includes at least one of F, N or Na, 1≤x≤6, 1≤y≤4, 0.5x≤m≤2x+y.

8. The positive electrode material according to claim 1, characterized in that The matrix includes a lithium transition metal composite oxide, wherein the composition of the lithium transition metal composite oxide is Li a Me b Co c O d-e T e , wherein Me includes at least one of Mn, Ni, Ti, Al, Mg, Fe, Cu, V, Mo, Zn, Zr or Cr, T is a halogen, 0.2≤a≤1.2, 0≤b≤1, 0 <c≤1,1≤d≤2,0≤e≤1。 9. An electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode comprises the positive electrode material according to any one of claims 1 to 8.

10. The electrochemical device according to claim 9, characterized in that The rock salt phase layer contains element A, and the electrolyte contains the element A, wherein A includes at least one of F, N or Na, and the difference between the mass percentage of element A in the rock salt phase layer and the mass percentage of element A in the electrolyte does not exceed 10%.

11. An electronic device, characterized in that: An electrochemical device comprising any one of claims 9-10.

Citation Information

Patent Citations

  • Positive electrode materials and electrochemical and electronic devices using them

    CN112421020B